Ilmu Nafs Dan Pemahaman Tentang Manusia Dalam Perspektif Alqur’an - Abdul Malik; Fitrah Sugiarto (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
Talking about the human soul remains interesting and relevant because it does not exist in a vacuum. There are three main things to note. First, the science of the human soul is related to dynamic human life. Second, talk about the human soul must be in line with the demands of the globalization era. Third, human nature must be creative and innovative. The psychology of Islamic education and talk about human beings is an important part. Humans are the subject and object of education. In an Islamic perspective, humans have two major tasks as servants of Allah SWT, namely total dedication to the Creator and the task of prospering the earth as caliphs. Humans have several comprehensive aspects, such as bodies, feelings, thoughts, and the complexity of the reality of life. Therefore, Islamic education must pay attention to all these aspects. Humans have two potentials facing each other, good and bad. In the context of Islamic Educational Psychology, psychology functions as a guide to develop good potential and control human bad potential. Aspects of the human psyche with all its potential is a manifestation of devotion to Allah SWT. The ultimate goal of Islamic Educational Psychology is to introduce humans to their God, so that they become people of faith and piety.